RANCANG BANGUN MODUL 3 PRAKTIKUM SISTEM EMBEDDED BERBASIS RASPBERRY PI (PERCOBAAN 3: PENGONTROLAN LAMPU MELALUI APLIKASI ANDROID) - Hindro Kusumo Wahid; Pratolo Rahardjo; Lie Jasa (Jurnal SPEKTRUM, 2021)
The role of university in supporting embedded system development and Internet Of Thingsimplementation seen with Embedded System + Lab Course in Electrical Engineering StudyPorgram, Engineering Faculty, Udayana University. Embedded System + Lab Course is a newcourse, so it’s not available yet learning tools in the terms of supporting the course, then it isnecessary to create Embedded System Practicum Module. Embedded System PracticumModule cosists of 4 kinds of experiment. 1st experiment: monitoring servo motor arm positionchange with PIR sensor in Android application. 2nd experiment: monitoring servo motor armposition change with ultrasonic sensor in Android application. 3rd experiment: controlling andmonitoring light bulb with Android application. 4th experiment: controlling and monitoring lightbulb with Telegram Bot. Given the many results of the discussion of experiments and subexperimentsin module 3, in this article, only experimental data 3 data will be discussed.Experimental data in 3rd module showing the success of tool performance and output datasuitability of monitoring and controlling lamp load status on Python Shell, Firebase and Androidapplication. Can be concluded in this research that the success of making 3rd ModuleEmbedded System Practicum(3rd Experiment : Lamp Controlling Through Android Application)has worked well. The overall experimental data can show the success of parsing JSON data onthe Python Shell platform, Firebase database, Android application.